Spain and the Catholic Church. Report of interview between the Archbishop of Westminster and some Catholics associated with the Labour and trade union movement : inter-departmental correspondence - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1936-11-04 019-0019-005 292/946/19/19(v)